Understanding and interpreting machine learning in medical image computing applications : first International Workshops, MLCN 2018, DLF 2018, and iMIMIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16-20, 2018, Proceedings /: first International Workshops, MLCN 2018, DLF 2018, and iMIMIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16-20, 2018, Proceedings. (2018) - Unknown
No abstract available